Allelopathic Effects of Ludwigia decurrens and L.adscendens Subsp. Diffusa on Germination, Seedling Growth and Yield of Corchorus Olitorious L. - Sakpere, Ayobola Moninuola; Oziegbe, Matthew; Bilesanmi, Idowu Arinola (Academic Press, 2014)
This study examined the allelopathic effect of Ludwigia decurrens and L.adscendens exudates on germination, seedling growth (hypocotyl and radicle elongation), seedling mortality vegetative growth and reproductive yield of Corchorus olitorious. Ludwigia decurrens, L. adscendens exudates and tap water (control) were applied to seeds of Corchorus olitorious over a period of 15 days and to 3 weeks old seedling for a period of 4 weeks. Ludwigia exudates had no inhibitory effect on the germination percentage of C. olitorious, but the exudates from the two Ludwigia spp. Induced mortality rate of the 15 day old seedlings (control: 5.00%, L. decurrens: 17.50%, L. adscendens: 26.88%) and a significant decrease in seedling elongation (hypocotyls and radicle length) of C. olitorious. For the vegetative growth experiment, results showed that the stem length, stem fresh weight and leaf area of C.olitorious were significantly inhibited during week 6 (P < 0.05) by L. decurrens and L. adscendens exudates. For reproductive yield experiment, number of pods per plant was significantly reduced on week. The high percentage mortality rate observed in seedlings might be an important factor in reducing seedling survival of Corchorus olitorious in habitats where the two Ludwigia spp are dominant.